DYNAMICS OF MEDIA AND SOCIETY INTERACTION IN COMMUNICATIVE SPACE - D. I. Chistyakov (Vestnik MGIMO-Universiteta)
The article is dedicated to the analysis of the social issues caused by mass-media impact on individuals and society. The author bases on reflection of sociological theories and discourses of late modern and postmodern and thus shows the transformation of media and their audience on the society’s way to the postmodernity. Postmodern media are viewed as a specific social institution of postmodernity; the author also emphasizes the basic peculiarities of its institutionalization. Structural integrity between mass-media and society is ensured through mass communication in its one-sided direction of the only communicator to the masses, often turning into an influence on recipients. The article stems from the premise that a modernday person is included in qualitatively and quantitavely other communications than in a preceding era of late modernity. Mass-media’s influence on society is thus specific. Messages, images, symbols, signs created by media not only form our perspective, but also serve as keys to the perception of reality. A subject today is involved in endless interconnected streams of information, hence a subject doesn’t consume information in discreet blocks anymore. Rather, we can imagine a subject standing knee-deep in a vast stream grabbing whatever he or she may find interesting. Under the certain conditions the very reality is being substituted by the virtual reality. The author shows and analyses the communication model of the basic information producers and recipients.